2024
DOI: 10.5713/ab.23.0200
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Mitragyna leaf extracts to be used as a bioactive compound source to enhance in vitro fermentation characteristics and microbial dynamics

Maharach Matra,
Srisan Phupaboon,
Pajaree Totakul
et al.

Abstract: Objective: <i>Mitragyna speciosa</i> Korth is traditionally used in Thailand. They have a high level of antioxidant capacities and bioactive compounds, the potential to modulate rumen fermentation and decrease methane production. The aim of the study was to investigate the different levels of microencapsulated-<i>Mitragyna</i> leaves extracts (MMLE) supplementation on nutrient degradability, rumen ecology, microbial dynamics, and methane production in an <i>in vitro</i> stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Matra et al 16 suggested that the supplementation of dragon fruit peel at 4% of total substrate could increase the gas production and ruminal fermentation. Similarly, Matra et al 22 revealed that the use of microencapsulated phytonutrients from Mitragyna leaf extracts could enhance gas production and ruminal fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Matra et al 16 suggested that the supplementation of dragon fruit peel at 4% of total substrate could increase the gas production and ruminal fermentation. Similarly, Matra et al 22 revealed that the use of microencapsulated phytonutrients from Mitragyna leaf extracts could enhance gas production and ruminal fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the elevated insoluble content could be a contributing factor to the higher gas production of (b). In a recent study, Matra et al 22 demonstrated that the supplementation of microencapsulated Mitragyna leaves extract at 4 to 6% DM in the diet led to increased gas (b) in an in vitro study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations